Combination scaffolds of salmon fibrin, hyaluronic acid, and laminin for human neural stem cell and vascular tissue engineering. (1st October 2016) - Arulmoli, Janahan; Wright, Heather J.; Phan, Duc T.T.; Sheth, Urmi; Que, Richard A.; Botten, Giovanni A.; Keating, Mark; Botvinick, Elliot L.; Pathak, Medha M.; Zarembinski, Thomas I.; Yanni, Daniel S.; Razorenova, Olga V.; et al.
Graphical abstract: Abstract: Human neural stem/progenitor cells (hNSPCs) are good candidates for treating central nervous system (CNS) trauma since they secrete beneficial trophic factors and differentiate into mature CNS cells; however, many cells die after transplantation. This cell death can be ameliorated by inclusion of a biomaterial scaffold, making identification of optimal scaffolds for hNSPCs a critical research focus. We investigated the properties of fibrin-based scaffolds and their effects on hNSPCs and found that fibrin generated from salmon fibrinogen and thrombin stimulates greater hNSPC proliferation than mammalian fibrin. Fibrin scaffolds degrade over the course of a few days in vivo, so we sought to develop a novel scaffold that would retain the beneficial properties of fibrin but degrade more slowly to provide longer support for hNSPCs. We found combination scaffolds of salmon fibrin with interpenetrating networks (IPNs) of hyaluronic acid (HA) with and without laminin polymerize more effectively than fibrin alone and generate compliant hydrogels matching the physical properties of brain tissue. Furthermore, combination scaffolds support hNSPC proliferation and differentiation while significantly attenuating the cell-mediated degradation seen with fibrin alone. HNSPCs express two fibrinogen-binding integrins, αVβ1 and α5β1, and several laminin binding integrins (α7β1, α6β1, α3β1) that can mediate interaction with the scaffold. Lastly, to test the ability of scaffolds to support vascularization, we analyzed human cord blood-derived endothelial cells alone and in co-culture with hNSPCs and found enhanced vessel formation and complexity in co-cultures within combination scaffolds. Overall, combination scaffolds of fibrin, HA, and laminin are excellent biomaterials for hNSPCs. Statement of Significance: Interest has increased recently in the development of biomaterials as neural stem cell transplantation scaffolds to treat central nervous system (CNS) injury since scaffolds improve survival and integration of transplanted cells. We report here on a novel combination scaffold composed of fibrin, hyaluronic acid, and laminin to support human neural stem/progenitor cell (hNSPC) function. This combined biomaterial scaffold has appropriate physical properties for hNSPCs and the CNS, supports hNSPC proliferation and differentiation, and attenuates rapid cell-mediated scaffold degradation. The hNSPCs and scaffold components synergistically encourage new vessel formation from human endothelial cells. This work marks the first report of a combination scaffold supporting human neural and vascular cells to encourage vasculogenesis, and sets a benchmark for biomaterials to treat CNS injury.